Pengaruh Revitalisasi Prasarana Terhadap Kualitas Pelayanan Di Puskesmas Mannanti - Hardiansyah, Hardiansyah; Hakim, Lukman; Mustari, Nuryanti (Universitas Muhammadiyah Makassar, 2021)
The purpose purposed to determine the effect of infrastructure revitalization on the quality of service at the Mannanti Health Center in Tellulimpoe Sub-District, Sinjai Regency. The type of research used quantitative descriptive research, while the data collection techniques used observation, questionnaire and documentation. While the opinions and perceptions of 20 respondents at the Mannanti Public Health Center in tellulimpoe sub-district, Sinjai Regency and 50 respondents from the community who used health services. Data Sources used primary data and secondary data, data analysis techniques were data reduction, data presentation and verification. The results showed that the Variable X Indicator of Infrastructure Revitalization got an average value of 38%vthat the indicators of the influence of Infrastructure Revitalization (physical interventions, economic rehabilitation and institutional revitalization) were good enough, Variable Y was obtained an average value of 63% in conclusion (Tangible, empathy, reliability, responsiveness and confidence) in the good category, and Variable infrastructure revitalization had a positive and significant effect explaining that the significant value of infrastructure revitalization was 0,000 less than 0.05 while the t count was 37,605.